THE RESULTS OF THE SURVEY AND CALCULATION OF ARCHED BRIDGE WITH RIBBED ARCHES TAKING INTO ACCOUNT THE ELASTIC FLEXIBILITY OF INTERMEDIATE SUPPORTS - Tarasenko, V. P.; Kosiak, V. M.; Rykina, V. L. (Science and Transport Progress, 2005)
The paper presents an analysis of technical condition, the calculation, taking into account pliability of the supports, and recommendations on reconstruction of the town arch bridge built in 1903 are presented.